Depositional Environment, Processes and Sequence Stratigraphy of the Paralic Helvetiafjellet Formation in Ullaberget, Southern Spitsbergen - Ahokas, Juha Matti (2004)
The Early Cretaceous, Barremian – Aptian Helvetiafjellet Formation is a well exposed paralic succession deposited at ramp-type shelf of the Borealic sea in the Svalbard region. The Ullaberget section in the Van Keulenfjorden area is an important reference section for the formation, due to excellent exposures and great variation in facies associations. The formation is in this locality subdivided in a lower, middle and upper portion. The lower boundary of the Helvetiafjellet Formation is a subaerial erosional unconformity, cut into the open-marine black shale of the Late-Jurassic – Early-Barremian Janusfjellet Subgroup. The erosional boundary is marked by a thin, discontinuous lag of fluvial channel conglomerate with extrabasinal clasts at the base of the Ullaberget Member. The Ullaberget Member is here suggested to be a tidally influenced delta introducing the Helvetiafjellet Formation, and not representing the top unit of the Rurikfjellet Formation in the Janusfjellet Subgroup, as previously published. The erosional unconformity represents a regional sequence boundary. The “Ullaberget delta” is a small delta, 11-18 m thick with an internal clinoform set, possibly formed as a bay-head delta during early sea level rise. The delta top facies is marked by a slight erosion which represents a bay or lacustrine ravinement surface which is succeeded by lacustrine or brackish-water mudstone, thin coal beds and thin crevasse or interdistributary bay sandstone units, overlain by thin fluvial channel sandstone beds. Crevasse and interdistributary bay sandstones have dinosaur foot imprints. The middle portion of the Helvetiafjellet Formation is up to 50 m thick and comprises the major part of the Helvetiafjellet Formation. The lower boundary is a transgressive ravinement surface capped by up to 12 m thick lentoid sandstone bodies with large sets of planar cross-stratification showing tidal influence. These bodies are interpreted as formed as tidal sand ridges of a local estuary. The ridges are overlain by heterolithic ...